2019
DOI: 10.1038/s41598-019-45585-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte PRMT1 protects from alcohol induced liver injury by modulating oxidative stress responses

Abstract: Protein Arginine methyltransferase 1 (PRMT1) is the main enzyme of cellular arginine methylation. Previously we found that PRMT1 activity in the liver is altered after alcohol exposure resulting in epigenetic changes. To determine the impact of these PRMT1 changes on the liver’s response to alcohol, we induced a hepatocyte specific PRMT1 knockout using AAV mediated Cre delivery in mice fed either alcohol or control Lieber-DeCarli liquid diet. We found that in alcohol fed mice, PRMT1 prevents oxidative stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 55 publications
(75 reference statements)
1
40
1
Order By: Relevance
“…We previously demonstrated that PRMT1 protects from alcohol‐induced liver injury and inflammation through regulation of oxidative stress response gene expression. ( 18 ) Here, we showed that PRMT1 knockout in an alcohol‐associated HCC model also resulted in an increase in number of TUNEL‐positive cells in the liver (Fig. 5A) and an increase in serum alanine aminotransferase (ALT) levels (5‐fold for male mice and 4‐fold in female mice) (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…We previously demonstrated that PRMT1 protects from alcohol‐induced liver injury and inflammation through regulation of oxidative stress response gene expression. ( 18 ) Here, we showed that PRMT1 knockout in an alcohol‐associated HCC model also resulted in an increase in number of TUNEL‐positive cells in the liver (Fig. 5A) and an increase in serum alanine aminotransferase (ALT) levels (5‐fold for male mice and 4‐fold in female mice) (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…These data were in accordance with the phenotype of hepatocyte‐selective PRMT1‐knockout mice fed alcohol, as described. ( 18 )…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations